LEARNING CLEAN AND HEALTHY LIVING BEHAVIOR WITH POP-UP BOOK AND POSTER MEDIA ON CHILDREN AGES 6-12 YEARS AT ELEMENTARY SCHOOL, MALANG - Naimah Naimah; Wahyu Setyaningsih (UNIVERSITAS AIRLANGGA, 2021)
Abstract Clean and Healthy Living Behavior (CHLB) is an effort to improve health quality through clean and healthy daily life behaviors. The problem of health behavior in children is related to personal hygiene, the environment, and the emergence of various diseases that often attack children. One of the preventive measures is to teach CHLB to children as early as possible by using interesting and easy-to-understand media for children. This study aims to determine the effect of a combination of a pop-up book and poster media on the ability of CHLB children aged 6-12 years. This study used a cross-sectional approach with 90 respondents divided into 3 groups. Collecting data using a questionnaire and analyzed by univariate, bivariate, and multivariate. The results showed that 66.67% of respondents had knowledge in the sufficient category and 10% in the less category before being given a combination of the two methods. Each respondent experienced a significant change in their knowledge. Statistical testing with MANOVA analysis on the comparison between treatment groups on knowledge, attitudes, and behavior obtained a calculated F value of 172,000 with a significance of <0.001 indicating that there were significant differences between treatment groups on knowledge, attitudes, and behavior. The use of pop-up books and posters can be used in the learning process because they have a major impact on increasing children's knowledge, attitudes, and behavior in an effort to maintain health through clean and healthy living behaviors.